STUDENTS’ MOTIVATIONAL FACTORS IN WRITING ESSAY - Hernina Dewi Lestari (Journey: Journal of English Language and Pedagogy, 2019)
This study aims at discovering the possible motivational factors affecting English Department students inwriting essay. Employing descriptive qualitative mode of research, the researcher tried to figure out theconcerning factors especially the motivational areas which possibly became the major support and/orhindrance for the students to write essay. To meticulously note down the result, the researcher made useof unstructured interview as the method of collecting the data. The result found teacher’s overallperformance, peers’ performance, parent’s involvement, and classroom ambience as the dominantmotivational factors affecting students’ performance in writing essay. Future researchers are suggested tostudy the more specific areas of motivational factors affecting students in writing essay to get better anddeeper understanding.